2015
DOI: 10.1111/medu.12880
|View full text |Cite
|
Sign up to set email alerts
|

Towards a pedagogy for patient and public involvement in medical education

Abstract: The authors highlight the need for a range of patient voices to be evident within such work, from its generation through to dissemination, in order that patients and the public are partners and not merely objects of this endeavour. To this end, this paper has been discussed with and reviewed by our own patient and public research partners throughout the writing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 24 publications
1
99
0
Order By: Relevance
“…50 Results here suggest International Medical Graduates and BME UK graduates were more likely to be separated from their social support network, causing stress and affecting their learning. This is worthy of further exploration as explaining, and reducing, differential attainment, is a key objective for the NHS and General Medical Council (GMC), among others.…”
Section: Discussionmentioning
confidence: 76%
“…50 Results here suggest International Medical Graduates and BME UK graduates were more likely to be separated from their social support network, causing stress and affecting their learning. This is worthy of further exploration as explaining, and reducing, differential attainment, is a key objective for the NHS and General Medical Council (GMC), among others.…”
Section: Discussionmentioning
confidence: 76%
“…17–19 Much less is known about the causes of the ethnic attainment gap among UK graduates (UKGs), and it is unclear whether IMGs and BME UKGs have experiences in common. A 2015 GMC-commissioned rapid review of the literature20 highlighted a lack of consensus and research about the causes of the ethnic attainment gap in UKGs. There is however general agreement that examiner bias or overt discrimination is unlikely to be the sole cause in examinations in medicine because differential attainment is seen in written machine-marked multiple choice examinations,21 and research into two postgraduate clinical examinations found no evidence of bias 22…”
Section: Introductionmentioning
confidence: 99%
“…The National Disability Strategy's second implementation plan, released in 2016, directed the need to 'ensure that the expressed views, lived experience and ongoing advice of people with disability are reflected in the development of policies and programs that affect their lives' (Department of Social Services, 2016, p. 16). This shift is evident not only in Australia, but also internationally (Regan de Bere & Nunn, 2016). This shift is evident not only in Australia, but also internationally (Regan de Bere & Nunn, 2016).…”
Section: Introductionmentioning
confidence: 84%